Environmental fate of (14)C radiolabeled 2,4-dinitroanisole ( DNAN) in soil microcosms - Olivares, Christopher I. (Environ Sci Technol, 2017)
2,4-dinitrosanisole (DNAN) is an insensitive munitions component replacing conventional explosives. While DNAN is known to biotransform in soils to aromatic amines and azo-dimers, it is seldom mineralized by indigenous soil bacteria. Incorporation of DNAN biotransformation products into soil as humus-bound material could serve as a plausible remediation strategy. The present work studied biotransformation of DNAN in soil and sludge microcosms supplemented with uniformly ring-labeled (14)C-DNAN to quantify the distribution of label in soil, aqueous, and gaseous phases. Electron donor amendments, different redox conditions (anaerobic, aerobic, sequential anaerobic-aerobic), and the extracellular oxidoreductase enzyme horseradish peroxidase (HRP) were evaluated to maximize incorporation of DNAN biotransformation products into the non-extractable soil humus fraction, humin. Irreversible humin incorporation of (14)C-DNAN occurred at higher rates in anaerobic conditions, with a moderate increase when pyruvate was added. Additionally, a single dose of HRP resulted in an instantaneous increased incorporation of (14)C-DNAN into the humin fraction. (14)C-DNAN incorporation to the humin fraction was strongly correlated (R(2)=0.93) by the soil organic carbon (OC) amount present (either intrinsic or amended). Globally, our results suggest that DNAN biotransformation products can be irreversibly bound to humin in soils as a remediation strategy, which can be enhanced by adding soil OC.